Dose-dependent modulation of hepatic cytochrome P450 enzymes by tenvermectin: implications for medication safety and combination therapy - Liang, Jianping; Cui, Can; Ren, Wenge; Li, Linglin; Lv, Linyi; Huang, Xianhui; Li, Xiangmei (Frontiers in Veterinary Science, 2025)
IntroductionTenvermectin (TVM) is a novel avermectin-class drug that has attracted attention for its superior antiparasitic potency, low toxicity, and broad-spectrum activity. However, uncertainty about its interaction with cytochrome P450 enzymes (CYPs) has raised concerns about potential therapeutic failure, increased risk of toxicity, dangerous drug combinations, and prolonged discontinuation periods.MethodTo address these critical safety concerns, we conducted a systematic comparative study using a highly selective and quantitatively accurate substrate conversion assay to assess and compare the effects of TVM and ivermectin (IVM) on the activities of key CYPs (CYP1A1/2, 2B1, 2C6, 2D2, and 3A1/2).ResultsTVM induced CYP1A, 2C, 2D and 3A activities only at high therapeutic doses (2.5 mg/kg), and its induction was significantly weaker than that of IVM at all doses tested, with the most pronounced difference for CYP3A1/2. Although TVM had weak inhibitory effects on CYP2B1 and 2D2, at therapeutic concentrations these effects are presumably unlikely to cause clinically significant CYP-mediated drug interactions.ConclusionAs the first study to report the effects of TVM on CYP enzyme activity, these findings provide important experimental evidence and a theoretical framework for its clinical safety assessment, development of optimal dosing regimens, and rational polypharmacy strategies.